Monetary Policy Transmission in the GCC Countries - Prasad, Ananthakrishnan (IMF Working Papers; Working Paper ;, 2012)
The GCC countries maintain a policy of open capital accounts and a pegged (or nearly-pegged) exchange rate, thereby reducing their freedom to run an independent monetary policy. This paper shows, however, that the pass-through of policy rates to retail rates is on the low side, reflecting the shallowness of money markets and the manner in which GCC central banks operate. In addition to policy rates, the GCC monetary authorities use reserve requirements, loan-to-deposit ratios, and other macroprudential tools to affect liquidity and credit. Nonetheless, a panel vector auto regression model suggests that U.S. monetary policy has a strong and statistically significant impact on broad money, non-oil activity, and inflation in the GCC region. Unanticipated shocks to broad money also affect prices but do not stimulate growth. Continued efforts to develop the domestic financial markets will increase interest rate pass-through and strengthen monetary policy transmission.